Multi-Resolution Modeling Method for Automated Material Handling Systems in Semiconductor FABs - Lee, Kwanwoo; Jeon, Woosung; Park, Sangchul (Proceedings - Winter Simulation Conference, 2023)
This paper presents a novel modeling framework for semiconductor fabrication facilities (FABs) that integrates production and material handling systems. Because the productivity of semiconductor FABs is significantly influenced by their material-handling systems, existing research has focused on optimizing operational logic considering both aspects. However, the scale and complexity of modern FABs make implementation of fully integrated models challenging, resulting in slow simulation speeds for long periods. To address this issue, we propose a multi-resolution modeling framework that creates material-handling system models at two distinct resolution levels, enabling fast, fully integrated FAB models while accounting for material-handling effects. Experimental results demonstrated accelerated simulation completion compared to single-resolution models while maintaining consistent results. The proposed method provides a practical approach for semiconductor FABs to investigate long-term phenomena and urgent decision-making problems while considering both production and material-handling systems.
Keywords: Automated material handling systems; Fully integrated; Integrated modeling; Materials handling systems; Model method; Modelling framework; Multiresolution modeling; Semi-conductor fabrication; Simulation speed; System models